History of Alcohol and Opioid Use Impacts on the Long-Term Recovery Trajectories of Methamphetamine-Dependent Patients - Tan, Haoye; Liang, Di; Zhong, Na; Zhao, Yan; Chen, Zhikang; Zhao, Min; Jiang, Haifeng (Frontiers in Psychiatry, 2019)
Methamphetamine (MA) has become one of the most widely used illicit substances in China and the rest of the world as well. Relapse, incarceration or death was observed after compulsory rehabilitation. However, the knowledge of recovery patterns among MA-dependent patients, early or late occurrence of these negative consequences (NC), is limited. The aims were to explore the long-term recovery patterns and associated factors among MA-dependent patients in Shanghai, China. MA-dependent patients discharged from Shanghai compulsory rehabilitation facilities in 2009 – 2012 were recruited in a baseline survey. The baseline data of 232 patients was then linked with their long-term follow-up data from official records. Group-based trajectory modeling (GBTM) was applied to identify distinctive trajectories of the occurrence of NC (incarceration, or readmission to compulsory rehabilitation, or death). Patients with monthly status data were found recovering with three distinctive trajectories: rare, late and early occurrence group. Multinomial logistic regression showed that having alcohol use history was associated with an increased likelihood of being in late occurrence group relative to rare occurrence group. Having opioid use history was associated with an increased likelihood of being early occurrence group relative to rare occurrence group. In addition, being female was associated with decreased likelihood of being in late occurrence group relative to rare occurrence group.